Developing Creative Abilities of Future Musical Art Teachers by Means of Choreography: An Experimental Study - Seheda, Natalia; Panchenko, Halyna; Chervonska, Liliia; Uskova, Alona (Journal of History Culture and Art Research, 2019)
The article contains the approaches of modern scholars to the definition of “creativity” and “creative abilities”. The experimental work method is determined and described with the introduction to methods of development of creative abilities. The pedagogical interpretation of the quantitative measurement of the experimental study results for developing the creative abilities of students in the experimental and control groups using the Student's t-test and Fisher's F-test is given. The authors discuss that creativity is developed on the basis of an interdisciplinary approach (integration of music methods and choreographic training), has an effective influence on the quality of the professional training of the future teacher of musical art.